The System of Wireless Smart House Based on GSM and ZigBee - Gao Mingming; Shaoliangshan; Huixiaowei; Sunqingwei (2010 International Conference on Intelligent Computation Technology and Automation, 2010)
GSM is combined with the new generation wireless network communication technology ZigBee, which established a wireless smart house system based on the GSM and ZigBee. The system refer to DSP chips to achieve controlling and monitoring the home applications, achieving to remote control and monitoring. This designment has reflected the characteristic of low cost, low power dissipation, great practical and good scalability.